Conceptual Design of a Hypersonic Vehicle Demonstrator - Buritica Yate, Juan C. (Cranfield University, 2025)
​​The development of airbreathing hypersonic vehicles presents additional technical challenges as the result of various design compromises in disciplines such as aerodynamics, propulsion, systems, and materials, all of which need to be integrated to produce a configuration that is not optimized for a specific speed region but provides enough performance to complete its mission. Given this added complexity to the design process, this paper presents a methodology applicable for conceptual design of airbreathing hypersonic vehicles covering the areas of parametric sizing, propulsion, aerodynamics, weights and balance, and trajectory. This methodology was used to develop the conceptual design of an airbreathing hypersonic vehicle demonstrator capable of cruising at Mach 5 at 80,000 ft with a 3500 nm range and a 10,000 lb payload. For this concept, hydrogen and hydrocarbon fuels were considered as well as two different body types: Wing Body and Blended Body. The effects of these design characteristics were assessed in the development of the propulsion system and the parametric sizing process. The propulsion analysis for the ramjet showed significant advantages of hydrogen over hydrocarbon fuel, as hydrogen presented 62.62% lower fuel consumption as well as 6.69% increase in specific thrust. During parametric sizing, it was found that Blended Bodies were lighter than Wing Bodies using the same fuel, due to having lower wetted surfaces areas and hence lower dry weights. When comparing the effects of fuel type, it was found that even though a hydrogen ramjet would consume less fuel in principle, the effects of its low density (74.6 kg/m3) produced Blended Body vehicle configurations with up to 47.1% heavier MTOW’s, 96% heavier dry weights, and 22.7% more fuel required for the same mission, structural and system characteristics as the Blended Body hydrocarbon vehicle. Based on these results, the chosen configuration was the Blended Body hydrocarbon. Using the values obtained from parametric sizing, the vehicle’s design was defined in the configuration layout phase and was evaluated for aerodynamics, propulsion and trajectory performance, from which it was determined that the vehicle could complete the mission.​
Keywords: Hypersonic; Conceptual Design; Parametric Sizing; Aerodynamics; Propulsion; Trajectory